Penyaluran FLPP kepada Masyarakat Berpenghasilan Rendah (MBR) dan Peran Penjamin dalam Mitigasi Gagal Bayar (Studi Literatur): Penelitian - Teuku Arif Ridwan; Siti Rakhman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Liquidity Facility for Housing Financing (FLPP) is a strategic policy initiated by the Indonesian government to improve access to home ownership for low-income communities (MBR) through subsidized mortgage loans. This study evaluates the effectiveness of the FLPP program and the critical role of credit guarantee institutions in mitigating default risks. Employing a qualitative content analysis method, the study reviews regulations such as POJK No. 2/2014 and No. 69/2016, along with various institutional reports and related literature. Findings reveal that, while FLPP has expanded housing access, there exists a significant gap between the official MBR income criteria (IDR 4–8 million) and bank lending requirements (IDR 7–14 million), particularly in densely populated urban areas like Jabodetabek. Credit guarantors play a vital role by covering up to 70% of credit risk, yet face limitations due to restricted capital and complex claim procedures. External factors such as Bank Indonesia’s interest rate fluctuations and rising property prices further exacerbate affordability challenges. The study concludes that FLPP sustainability requires more inclusive policies, strengthened guarantor institutions, and collaborative efforts among the Financial Services Authority (OJK), financial institutions, and local governments to ensure that the program remains well-targeted and impactful.